2020
DOI: 10.1177/2150132720937831
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Skin Lesions Using Photographs Taken With a Mobile Phone: An Online Survey of Primary Care Physicians

Abstract: Skin conditions are one of the most frequent reasons for visiting a primary health care facility, making it of vital importance that general practitioners (GPs) have the right knowledge and tools to diagnose the most frequent dermatological conditions. Methods: This study evaluates the accuracy of dermatological diagnoses made by 120 GPs based on photographs taken with a smartphone by an anonymous online cross-sectional survey. Results: The study was carried out between August and October 2018. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Teledermatology is an important subspecialty of telemedicine that continues to evolve with advances in telecommunication and mobile phone technology 1. Patients with skin disorders, which account for over 13 million primary care consultations each year,2 3 have been targeted for this new way of working, as the skin is uniquely visible to the naked eye. The COVID-19 pandemic has led to several changes to the way we deliver healthcare, none more so than in general practice which has made every effort to reduce contact between staff and patients by efficiently triaging and switching to consultation by telephone 4.…”
Section: Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Teledermatology is an important subspecialty of telemedicine that continues to evolve with advances in telecommunication and mobile phone technology 1. Patients with skin disorders, which account for over 13 million primary care consultations each year,2 3 have been targeted for this new way of working, as the skin is uniquely visible to the naked eye. The COVID-19 pandemic has led to several changes to the way we deliver healthcare, none more so than in general practice which has made every effort to reduce contact between staff and patients by efficiently triaging and switching to consultation by telephone 4.…”
Section: Problemmentioning
confidence: 99%
“…Restrictions imposed by the COVID-19 pandemic have further increased its application and use as a tool for the rapid and effective diagnosis of skin disorders 11. Recent reports have shown that a self-selected group of general practitioners (GPs), looking exclusively at photographs taken by a dermatologist using a Samsung J7 smartphone, were able to make a correct diagnosis in 64% of skin lesions 3. In another study, patient images which were taken by GPs using specialist magnifying devices and sent to a consultant dermatologist, were assessed within 48 hours.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional survey evaluating the accuracy of dermatological diagnoses based on photographs taken with a mobile device demonstrated multiple false positives and a drop in diagnostic specificity to 50% when compared with face-to-face diagnosis. 8 It is difficult to draw any conclusions about the efficacy of medical photography using mobile devices as there are such varying degrees of user proficiency. Diagnostic specificity may be improved by training general practitioners to acquire greater diagnostic knowledge through medical photographs.…”
Section: Accuracy In Capturementioning
confidence: 99%
“…The question then becomes whether a mobile device makes poorer photographic technique more likely. A cross-sectional survey evaluating the accuracy of dermatological diagnoses based on photographs taken with a mobile device demonstrated multiple false positives and a drop in diagnostic specificity to 50% when compared with face-to-face diagnosis 8…”
Section: Accuracy In Capturementioning
confidence: 99%
“…In an interesting study, Marin-Gomez et al 1 examined the utility of digital clinical photography in facilitating general practitioners and primary care teams diagnose and manage dermatological conditions. In the current COVID-19 pandemic where social distancing measures preclude the traditional face-to-face consultation delivery model, the topic discussed by the authors is more pertinent than ever before.…”
mentioning
confidence: 99%